Forecasted stability of Mediterranean evergreen species considering global changes - GRATANI, L.; Bombelli, A. (GLOBAL CHANGE AND PROTECTED AREAS, 2001)
Plant communities of the Mediterranean climate Regions are exposed tohigh temperatures, high radiation and water stress during summer, they are dominated by evergreen sclerophyllous species and drought semi deciduous species. To define the adaptive strategies, anatomical and morphological leaf traits of Quercus ilex L., Phillyrea latifolia L. (typical evergreen sclerophyllous species) and Cistus incanus L., (a drought semi deciduous species), growing in the Mediterranean maquis along Pome's coast line (Italy) were analysed. The typical evergreen sclerophyllous species have long leaf life span (from 1 to 4 years), steeper leaf inclination (average 56 degrees), higher specific leaf mass (average 21.3 mg cm(-2)) and the highest leaf thickness (average 324 mum). The semi deciduous species have a lower leaf life span (from 4 to 8 months), a lower leaf inclination (44 degrees +/- 13 degrees), a lower specific leaf mass (14.7 +/-1.5 mg cm(-2)) and a lower leaf thickness (244 +/- 15 mum). The more xeromorphyc species (Q. ilex and P. latifolia) may be at a competitive advantage considering the forecasted air temperature increase in the Mediterranean basin. Increasing drought stress may in fact determine a shortening of leaf life span that may prove to be critical for C. incanus. Knowledge of plant response to stress factors is important in the perspective of climatic changes.
Meeting on Global Change and Protected Areas, LAQUILA, ITALY, SEP, 1999Meeting on Global Change and Protected Areas, LAQUILA, ITALY, SEP, 1999The following values have no corresponding Zotero field: periodical: GLOBAL CHANGE AND PROTECTED AREAS pub-location: PO BOX 17, 3300 AA DORDRECHT, NETHERLANDS
Keywords: Q. ilex; P. latifolia; C. incanus; leaf life span